Chinese-American Liminality in Everything, Everywhere All at Once (2022): Between Violence and Wu Wei - Alexei Wahyudiputra; Antonius Rahmat Pujo Purnomo (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Diasporas are often said to live in “two worlds”. The conflicting relationship between their physical and mental states results in a fissure where symbolic and physical violence become the main drive for diaspora to survive. This violence comes not only due to these diaspora’s own inner conflicts, but also due to the discrepancies between their native and internalized culture with the external norms and values that surround them in their current stay. The theme of diaspora and violence has been recurrent in American cinematic representation. As the most recent example, an independent film entitled Everything, Everywhere All at Once delves into this issue by incorporating a storyline of a Chinese-diasporic family in the United States who encounters various problems regarding their cultural differences to their surroundings. This article seeks to examine the cultural dynamics only of Evelyn, Waymond, and Joy in the film’s storyline amidst the abundance of multiversal plot points that serve as the pivotal exposition in the film. The analyses are textually grounded based on Homi Bhabha’s notion of liminality and contextually on the differing conception of violence in Chinese and American contexts respectively. This article draws from a Taoist concept of Wu wei to interpret the latter point. This study finds that the film represents diasporic characters within a liminal space that forces them to produce their own “maneuver” in order to survive. The parental problems that Evelyn has with Joy as well as her familial and ideological problems with Waymond are found to be propelled by such culturally-laden maneuvers. The film then can be read as an allegory of Chinese-American diaspora’s liminal experience in the United States. This allegory contains an ethical stance where the idea of non-violence (wu wei) becomes the utopian message of the film.